Sexual orientation and household savings: Do homosexual couples save more? - Brighita Negrusa; Sonia Oreffice (Institute for the Study of Labor (IZA), 2010)
We analyze how sexual orientation is related to household savings using 2000 US Census data, and find that gay and lesbian couples own significantly more retirement income than heterosexuals, while cohabiting heterosexuals save more than their married counterparts. In a household savings model, we interpret this homosexual-specific differential as due to the extremely low fertility of same-sex couples, in addition to the precautionary motives driving cohabiting households to save more than married ones. Evidence from homeowners' ratio of mortgage payments to house value exhibits the same pattern of savings differentials by sexual orientation and cohabiting status.
Keywords: D1; D12; J15; J16; 330; Sexual orientation; household savings; retirement; housing; Sparen; Alterssicherung; Haushaltsökonomik; Homosexualität; Schätzung; USA